Pro JPA 2 - Keith, Mike. (Apress : Imprint: Apress, 2013)
Pro JPA 2, Second Edition introduces, explains, and demonstrates how to use the new Java Persistence API (JPA) 2.1 from the perspective of one of the specification creators. A one-of-a-kind resource, it provides both theoretical and extremely practical coverage of JPA usage for both beginning and advanced developers. Authors Mike Keith and Merrick Schincariol take a handson approach, based on their wealth of experience and expertise, by giving examples to illustrate each concept of the API and showing how it is used in practice. The examples use a common model from an overriding sample application, giving readers a context from which to start and helping them to understand the examples within an already familiar domain.After completing the book, you will have a full understanding of JPA and be able to successfully code applications using its annotations and APIs. The book also serves as an excellent reference guide during initial and later JPA application experiences. Hands-on examples for all aspects of the JPA specification Expert insight about various aspects of the API and when they are useful Portability hints to provide increased awareness of the potential for nonportable JPA code